2019
DOI: 10.5296/jei.v5i2.14747
|View full text |Cite
|
Sign up to set email alerts
|

Dual Language Program Models and English Language Learners: An Analysis of the Literacy Results from a 50/50 and a 90/10 Model in Two California Schools

Abstract: This paper examines the literacy results of English language learners (ELLs) in two California schools following either the 50/50 or the 90/10 dual language (DL) program model. The purpose of this paper is to provide a literature review of dual language programs with an analysis of two schools’ websites and literacy assessment data in order to determine the effectiveness of each program model in establishing strong foundational literacy skills and fostering the prolonged academic success of ELLs. California pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…These results suggest that the benefit of additional exposure to Spanish does not come at a cost to the children's English language development. Such results are consistent with previous studies on language development in dual-language immersion programs that reported that increased exposure to Spanish has a positive impact on the development of both languages (e.g., Acosta et al, 2019;Lindholm-Leary & Howard, 2008;Marian et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that the benefit of additional exposure to Spanish does not come at a cost to the children's English language development. Such results are consistent with previous studies on language development in dual-language immersion programs that reported that increased exposure to Spanish has a positive impact on the development of both languages (e.g., Acosta et al, 2019;Lindholm-Leary & Howard, 2008;Marian et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Immersive bilingual schooling has become increasingly popular in the United States, with over 2,000 dual-language immersion programs offering instruction in English and a partner language nationwide in 2017 (Steele et al, 2017). Such programs have proven to be effective in supporting language development in two languages, and have also been shown to improve bilingual students' academic performance (e.g., Acosta et al, 2019;Lindholm-Leary & Howard, 2008;Marian et al, 2013). While there is recent work on the acquisition of grammatical gender and verbal morphology by child heritage bilinguals in dual language immersion programs (Montrul & Potowski, 2007;Fernández-Dobao & Herschensohn 2020), syntactic development in children enrolled in immersion schooling remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of DLI goes well beyond HL acquisition itself. In addition to honoring the linguistic rights of HSs (Skutnabb-Kangas 2006), DLI has been shown to benefit Hispanic students' academic performance as measured using standardized assessment scores (e.g., Lindholm-Leary and Borsato 2005;Marian et al 2013;Serafini et al 2020) and is at least as effective in fostering the acquisition of English (e.g., Acosta et al 2019;Marian et al 2013;Umansky and Reardon 2014). DLI also expedites the development of executive functioning skills (e.g., Garraffa et al 2020;Nicolay and Poncelet 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, instruction in English helps students "develop oral language proficiency," as well as "some preliteracy" (Lindholm-Leary, 2012, as cited in Billy & Garríguez, 2019, p. 109). The 90:10 program model was originally tailored toward students who speak the partner language (e.g., Spanish, Acosta et al, 2019). Therefore, there is a heavier emphasis on Spanish in earlier grades, with a transition to equal emphasis of both English and Spanish later to fully support bilingualism and biliteracy.…”
Section: A Types Of Dual Language Program Modelmentioning
confidence: 99%
“…3) The 50:50 model: One other common type of dual language program model is the 50:50 model. In this model, teaching and learning are equally divided between English and Spanish (Acosta et al, 2019;Billy & Garríguez, 2019;Cole, 2015). The 50:50 model generally promotes a "'simultaneous literacy' model," developing literacy in the target language and English at the same time (Dual Language Immersion Planning Guide, n.d., 50:50 Model section).…”
Section: A Types Of Dual Language Program Modelmentioning
confidence: 99%